Inequality, Economic Growth, and Redistribution; Literature Review - Muhammad Hidayat; Syafruddin Karimi (Akuntansi & Ekonomika, 2020)
Economists have long believed that economic growth will solve the problem of inequality and poverty. For decades, the question of whether and how inequality affects growth has been the subject of open debate in the academic world. In the same section, the redistribution which is considered part of the equalization step also has positive and negative impacts on economic growth. This paper presents a literature review consisting of several sections including: 1) literature review on the relationship between inequality and growth; 2) the relationship between redistribution and growth; 3) even distribution of infrastructure is part of the form of redistribution.